Southern right whale (Eubalaena australis) mortalities and human interactions in Australia, 1950-2006 - Kemper , Catherine; Coughran , Douglas; Warneke, Robert; Pirzl , Rebecca; Watson , Mandy; Gales , Rosemary; Gibbs , Susan (J. Cetacean Res. Manage., 2023)
A total of 44 records of southern right whale mortalities and non-fatal anthropogenic interactions have been documented in Australia by museums, wildlife agencies and researchers since 1950. Sixteen of the events involved whales that apparently survived. Events were recorded in all months except January and 65% occurred in the period July to October. Mortalities were more numerous in the western half of the continent where southern right whales are more frequently observed. Events were classified according to their outcome and nature: carcasses (with no evidence of human interaction) n=25, fatal entanglements n=1, non-fatal entanglements n=12, fatal vessel collisions n=2, non-fatal vessel collisions n=3, non-fatal shooting n=1. No live strandings were recorded. The number of both mortalities and non-fatal anthropogenic incidents has increased 4-fold since the mid 1970s. More calves than ‘non-calf’ whales were present in the carcass category, whereas the opposite was the case for events involving human interaction. Lines, nets and buoys used in fishing crustaceans (rock-lobster, crab) were associated with several entanglements (n=5). A longline entanglement of a 14m female resulted in a chronic injury, debilitation and death. As a proportion of the total records for each region, there were fewer vessel collisions of right whales in Australia (11%) than in South Africa (16%) or the North Atlantic (35%).